An assessment of mobile phone-based dissemination of weather and market information in the Upper West Region of Ghana - Etwire, Prince M.; Buah, Saaka S.J.; Ouédraogo, Mathieu; Zougmoré, Robert B.; Partey, Samuel T.; Martey, Edward; Dayamba, Sidzabda Djibril; Bayala, Jules (Springer, 2017)
The rapid growth of mobile phones in Ghana has opened up the possibility of delivering timely and useful weather and market information to farmers at costs lower than traditional agricultural extension services. In this paper, we assess the usefulness, constraints, and factors likely to influence farmers’ decisions to patronize mobile phone-based weather and market information.